P1788FACTORS AFFECTING EGFR SLOPE IN KIDNEY TRANSPLANT RECIPIENTS DURING 48 MONTHS AFTER TRANSPLANTATION. (6th June 2020) - Rambabova Bushljetikj, Irena; Dohcev, Saso; Mojsova Mijovska, Maja; Stavridis, Sotir; Stankov, Oliver; Spasovski, Goce
Abstract: Background and Aims: After the first year following kidney transplantation approximately 3-5% of grafts fail each consecutive year. Many factors have impact on the graft function and only a few may be modifiable. Monitoring of the graft function by serum creatinine concentrations and estimated glomerular filtration rate (eGFR) are recommended methods for evaluation. The aim of the study was to assess the decline of graft function defined by change in the annual eGFR slope and factors that might affect it. Method: A total number of 55 adult patients with living donor kidney transplant (LDKT) were included in the study. The inclusion criteria were: first transplantation of one organ - kidney, use of living donor related or unrelated (emotionally related - spouses) donor. Clinical and biochemical variables, serum creatinine, BUN, protein status, 24 hours proteinuria and body weight were analyzed at 12, 24, 36 and 48 months after transplantation. The Nankivell equation for estimating glomerular filtration rate was used to calculate the slope of renal function over time (1 to 4 years post-transplantayion) by linear regression analysis. Results: Out of 55 kidney transplant recipients 18 (33.3%) were female. The majority of transplants had good function (eGFRNankivell ≥ 60 ml/min) at 1 year. The average GFR at 12 months was 67.81±16.7 mL/min/1.73 m 2 with majority of patients at stage 2 of chronic kidney disease classification. Thirty eight patients had eGFR slope <5ml/min/year and 12 patients had a higher slope ( >5ml/min/year). Only 5 patients (∼ 9%) have graft failure during the period of follow up of 48 months. The average slope decline calculated with linear regression analysis was -3.42 ± 3.2 mL/min/year (range -12.38 – 3.29 ) (slope ± standard error). Proteinuria was predictive for worsening of the graft function. Rapid progressors have been associated with a higher proteinuria at 24 and 48 months: 0.35 ± 0.39 g/24h, median 0.24 (range 0.11 – 0.43 g/24h) and 0.49 ± 0.59 g/24h, median 0.31 (range 0.14 – 0.48 g/24h), (p=0.044 and p=0.021, respectively). Younger patients have more rapid eGFR slope decline (slope (-7.81 ± 2.12 vs. -2.40 ± 1.3, mL/min/year, p=0, 0001). The mean recipient age in the group with stabile eGFR slope was 37.59± 8.7, and in the group with rapid progression was 29.1 ± 8.6 years (p=0.0046). Conclusion: Proteinuria after kidney transplantation has been identified as a risk factor associated with poor graft survival. Younger renal transplant recipients are associated with more rapid decline of the graft function that could be partially explained with their more potent immune response